Impact of Formative Feedback on Skill Acquisition in Simulation-Based Training: Formative Feedback on Skill Acquisition in Simulation-Based Training - Awan, Amara Hayat; Abdullah, Zainab; Baig, Muhammad Zeeshan; Parvez, Farida; Jabeen, Nadia; Gul, Naveed (Pakistan Journal of Health Sciences, 2025)
Simulation-based learning is widely used in healthcare education to teach clinical skills in a safe, structured environment. However, the integration of systematic formative feedback within simulation remains inconsistent, particularly in undergraduate programs. Objectives: To evaluate the impact of structured formative feedback on clinical skill acquisition, self-reported confidence, and learner satisfaction among undergraduate students in medicine, dentistry, and nursing. Methods: A quasi-experimental study was conducted at Rawal Institute of Health Sciences with 72 undergraduate students. Participants were recruited via convenience sampling and randomly assigned to either a feedback group or a control group (n=36 each). Both groups performed the same simulation tasks, but only the feedback group received structured, real-time formative feedback after the initial assessment. Data collection included pre- and post-test knowledge scores, Objective Structured Clinical Examination (OSCE) performance, confidence rating scales, and satisfaction questionnaires. Data were analyzed using SPSS version 26.0. Results: The feedback group showed significantly higher post-test and OSCE scores compared to the control group (p<0.001), with large effect sizes (Cohen’s d >1.5). Improvement scores and post-training confidence ratings were also significantly greater in the feedback group. Learner satisfaction scores in the feedback group were consistently high across all domains. Conclusions: Structured formative feedback in simulation-based training leads to substantial improvements in clinical performance, learner confidence, and satisfaction. These findings support the routine incorporation of feedback into undergraduate simulation curricula, particularly in resource-limited educational settings.